Teaching Beyond Connectivity: A Year Comparing Blended and Face-to-face Learning in a Secondary Classroom - Nigel V Smith (New Zealand Journal of Teachers' Work)
This article reflects and explores the findings of a year-long mixed methods research project in a New Zealand secondary classroom exploring social connectedness and blended learning. The performance and perceptions of students in two classes, in the same subject and taught by the same teacher, were compared to explore the differential impact of blended or face-to-face teaching modalities. Teacher reflections throughout the year are used to draw out surprising discrepancies between empirical findings and teacher perceptions. Further reflection on the nature of teacher-student relationships in blended learning contexts is informed by both theory and the experiences of students and the teacher who participated in the project.